Quality of life in university professors: association with components of spirituality and professional achievement - Borges, Cezimar Correia; Maciel, Renata Custódio; Lemes, Uitarany do Prado; Noll, Matias; Barbosa, Maria Alves; Porto, Celmo Celeno; dos Santos, Patrícia Roberta; Lucchetti, Giancarlo; Silva, Weder Alves; Ribeiro, Celaine; Aprigliano, Vicente; Silveira, Marina; et al. (Frontiers in Psychology, 2026)
BackgroundUniversity professors face considerable workload pressures and professional demands that can negatively affect their quality of life (QoL). Positive emotions associated with spirituality and religiousness (S/R) have been linked to enhanced QoL in various populations; however, limited research has explored this relationship among university professors.ObjectiveTo examine the association between spirituality/religiousness and quality of life among university professors, identifying the most influential spiritual facets and relevant sociodemographic predictors.MethodsThis cross-sectional study included 213 professors from a public university in Goiás, Brazil. Participants completed the WHOQOL-BREF (QoL) and WHOQOL-SRPB (S/R) instruments, both validated for the Brazilian population.ResultsSeven of the eight S/R facets showed significant positive correlations (p ≤ 0.01) with QoL domains. The strongest associations were observed in the psychological domain, particularly for hope and optimism (r = 0.67), spiritual strength (r = 0.62), and faith (r = 0.59). Regression analyses indicated that these facets were the strongest independent predictors of overall QoL (R2 = 0.28). Professional and sociodemographic factors such as academic degree, job satisfaction, professional recognition, and income were also associated with higher QoL, while holding multiple employment contracts was inversely related to it.ConclusionHigher levels of S/R were positively associated with QoL among university professors. These findings highlight the potential value of integrating spirituality-based activities into university wellness programs as effective strategies to promote well-being and help faculty manage occupational demands.